Political Quixoticism - Stern, Adam Y. (The journal of religion, 2015)
This essay discusses the political quixoticism of philosophers Carl Schmitt and Walter Benjamin. Topics discussed include the relationship between the two philosophers, their fascination on the concept of Romanticism, the significance of Don Quixote as a philosophical and literary figure in the 19th-century German philosophy and the character as a radical counterpoint of the circumspection and realism of the political theologians.